Ebatan: Keaslian sebagai Daya Tarik Wisata Gastronomi Berbasis Komunitas - Aryan Agus Pratama; Hastuti Nurhayati; Baiq Nikmatul Ulya; Pahrul Azim (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
Lombok tourism is known for its authentic cultural richness, but the potential of traditional culinary such as Ebatan has not been optimally utilized as a gastronomy tourism attraction. This research aims to explore the authenticity of Ebatan as a community-based gastronomy tourism attraction in Lombok. This research uses a qualitative approach with data collection techniques through the ngayo method, which includes participatory observation and in-depth interviews with traditional leaders, cultural experts, and local communities. Data analysis was done thematically through the stages of data condensation, presentation, and conclusion drawing. The results showed that Ebatan has a high level of authenticity, both in terms of culinary identity and symbolic values passed down through traditional authority. The central role of the local community is reflected in efforts to maintain and transmit these values, which at the same time makes Ebatan a representation of cultural identity. This research confirms that Ebatan has great potential to be developed as a community-based gastronomic tourism attraction, designed to provide an authentic experience while supporting the preservation of Lombok's distinctive culinary heritage.